2005
DOI: 10.1677/jme.1.01657
|View full text |Cite
|
Sign up to set email alerts
|

βA- and βC-activin, follistatin, activin receptor mRNA and βC-activin peptide expression during rat liver regeneration

Abstract: The mRNA expression of two activin growth factor subunits ( A-and C-activin), activin receptor subunits (ActRIIA, ActRIIB) and the activin-binding protein follistatin, and peptide expression of A-activin and C-activin subunits, were examined in regenerating rat liver after partial hepatectomy (PHx). Liver samples were collected from adult, male Sprague-Dawley rats, 12-240 h (n=3-5 rats per time point) after PHx or from sham-operated controls at the same time points. Hepatocyte mitosis and apoptosis were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 37 publications
4
42
0
Order By: Relevance
“…By immunohistochemistry, significant activin beta C expression has been detected in cells from additional organs, including the prostate, ovary, testes, and pituitary gland [10,77] . After partial hepatectomy, a transient downregulation of activin beta C expression was observed by several studies [42,44,78,79] . We have found reduced activin beta C expression in HepG2 and Hep3B hepatoma cells versus normal liver tissue [80] and a drop of beta C expression was also described in rat hepatocytes during primary culture with and without EGF treatment [44] .…”
Section: Beta C and Beta Ementioning
confidence: 91%
See 3 more Smart Citations
“…By immunohistochemistry, significant activin beta C expression has been detected in cells from additional organs, including the prostate, ovary, testes, and pituitary gland [10,77] . After partial hepatectomy, a transient downregulation of activin beta C expression was observed by several studies [42,44,78,79] . We have found reduced activin beta C expression in HepG2 and Hep3B hepatoma cells versus normal liver tissue [80] and a drop of beta C expression was also described in rat hepatocytes during primary culture with and without EGF treatment [44] .…”
Section: Beta C and Beta Ementioning
confidence: 91%
“…In contrast, in AML12 cells, an immortalized mouse hepatocyte cell line, and in primary rat hepatocytes activin beta C increased DNA synthesis [84] . Adenovirus-mediated expression of activin beta C accelerated liver regeneration after partial hepatectomy in rats [85] and association of activin beta C immunoreactivity with mitotic hepatocytes was observed in regenerating liver after partial hepatectomy [42] . Activin C does not activate activin A-responsive promoters and it was suggested that the beta C subunit down-regulates the levels of bioactive activin A via the formation of signaling-incompetent activin AC heterodimers in PC3 human prostate cancer cells [9,86] .…”
Section: Beta C and Beta Ementioning
confidence: 95%
See 2 more Smart Citations
“…In carbon tetrachloride (CCl 4 ) treated rat liver, activin A is expressed in hepatocytes and more intensively in hepatic stellate cells (HSC), which secrete excessive extracellular matrix and play a pivotal role in the pathogenesis of liver fibrosis [21][22][23]. In these rats, strong immunoreactivity of activin A is observed in HSC transformed into an activated form of myofibroblasts [21].…”
Section: Livermentioning
confidence: 99%